Pengembangan Ilmu Pendidikan Islam Anak Usia Dini (Berkisah Membangun Dunia yang Damai) - Fatmawati, Fatmawati (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2018)
Development in a national education based on a paradigm that builds the Indonesian nation asa whole that functions an object that has the capacity to actualize in the potential anddimensions of humanity optimally, directed to improve the quality and competitiveness ofhuman resources. Education is a form of learning institution that takes place in the family,school, and community environment to develop abilities as optimal as possible from birth to theend of life in education during the birth period until the age of six years is known as earlychildhood education.